SISTEM PENGENDALIAN INTERN SIMPAN PINJAM ANGGOTA KSP PRIMKOPPABRI WELERI - Munifah Munifah; Haris Ihsanil Huda (Program Studi Sistem Informasi, Universitas Banten Jaya, 2024)
PRIMKOPPABRI Weleri Savings and Loans Cooperative is a savings and loans cooperative which has a mission to improve the welfare of its members. In Montongsari Village, Weleri District, Kendal Regency, there is the PRIMKOPPABRI Weleri Savings and Loans Cooperative. Based on interviews with cooperatives, there are still several weaknesses in the internal control process. These shortcomings include prospective members of the cooperative having to fill out a Form to register to become members, customer data processing which is still carried out using written media in the Form of an application Form, archiving is carried out, as well as other processing problems in writing so that the process of disbursing customer data must be done one by one or individually sheets to find the location of customer data and savings and loan inFormation, daily and monthly transaction processes are made in different files so that admins have difficulty making financial reports. Therefore, with an internal control system, you can monitor member data, simplify the process of applying for savings and loans and presenting financial reports automatically.